Epigenetic targeting DNMT1 of pancreatic ductal adenocarcinoma using interstitial control release biodegrading polymer reduced tumor growth through hedgehog pathway inhibition. (January 2019) - Huang, Mao-Hsuan; Chou, Yi-Wen; Li, Ming-Hsun; Shih, Tina E.; Lin, Shinn-Zong; Chuang, Hong-Meng; Chiou, Tzyy-Wen; Su, Hong-Lin; Harn, Horng-Jyh
Graphical abstract: Abstract: Annually, 48, 000 people die from pancreatic ductal adenocarcinoma (PDAC), ranking it the fourth among cancer-related deaths in the United States. Currently, anti-cancer drugs are not effective against PDAC, and only extends survival by 3 months. Aberrant DNA methylation has been shown to play an important role during carcinogenesis in PDAC, with approximately 80% of tumor overexpressing the DNA methyltransferase 1 (DNMT1) protein. In the present study, we used DNMTs as a screening platform to find a new DNMT inhibitor, n-butylidenephthalide (n-BP), which is identified from a Chinese herbal drug. n-BP could inhibit DNMT1 expression in both dose-dependent and time-dependent manner. It also displays an effect in suppressing growth of PDAC cells and inducing cell cycle arrest at G0/G1 phase leading apoptosis. Growth suppression can be restored by the overexpression of DNMT1 in PDAC cells. Furthermore, we found n-BP-mediated DNMT1 suppression influenced the protein stability rather than changing the RNA expression. Through microarray studies, we found that the patched domain contained 4 (PTCHD4) is the potential downstream gene of DNMT1. Following silencing of PTCHD4 expression by siRNA, n-BP decreased tumor growth inhibition. Finally, in vivo, two animal models were used to evaluate the efficacy and survival after n-BP treatment by interstitial control release polymer delivery. The results show that n-BP could effectively inhibit PDAC tumor volume growth and extend animal survival. In summary, n-BP may inhibit the growth of human PDAC cells though reducing DNMT1 and increasing the expression of PTCHD4 both in vitro and in vivo.